2009
DOI: 10.1029/2009ja014357
|View full text |Cite
|
Sign up to set email alerts
|

Ion temperature drop and quasi‐electrostatic electric field at the current sheet boundary minutes prior to the local current disruption

Abstract: [1] From a survey of the cross-tail current disruption (CD) events in the near-Earth plasma sheet collected from the Time History of Events and Macroscale Interactions during Substorms (THEMIS) mission, we identify a highly repeatable class of event occurring at the current sheet boundary in a few minutes before the local CD onset. Salient features of this class of event include (1) a precipitous drop of the ion temperature, (2) concurrent growth of a neutral sheet-pointing electric field, and (3) ULF wave act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 73 publications
(127 reference statements)
4
40
1
Order By: Relevance
“…12. The latter seems to line up with a result from a survey performed by Liang et al, [30] in the near-Earth plasma sheet. They studied cross-tail current disruption (CD) events and identified that "when the current sheet thickness is down to ion kinetic scales, the ions are demagnetized, and a quasi-electrostatic neutral sheetpointing electric field emerges (at the current sheet boundary) owing to the charge separation".…”
Section: Physics Of the Harang Discontinuity (Hd)supporting
confidence: 85%
“…12. The latter seems to line up with a result from a survey performed by Liang et al, [30] in the near-Earth plasma sheet. They studied cross-tail current disruption (CD) events and identified that "when the current sheet thickness is down to ion kinetic scales, the ions are demagnetized, and a quasi-electrostatic neutral sheetpointing electric field emerges (at the current sheet boundary) owing to the charge separation".…”
Section: Physics Of the Harang Discontinuity (Hd)supporting
confidence: 85%
“…Such bell‐shaped T i profiles were obtained by Catapano et al [] for the special type of ion velocity distributions. Similar profiles could be resulted from some combination of hot (current carrying) particle population and cold background population (see corresponding CS model in Yoon and Lui [] and Liang et al []). The scenario of plasma parameter projection along magnetic field lines predicts that the ion population observed at CS boundaries around r ∼ 10 R E with T B <3 keV travels along magnetic field lines from the distant tail r > 45 R E , where T 0 <3 keV.…”
Section: Discussionmentioning
confidence: 65%
“…The real configuration could be of course more complicated. In addition to these two particle groups a “third” relatively cold plasma component with substantial density is often observed [ Liang et al , 2009; Artemyev et al , 2009]. Zhou et al [2009] and Liu et al [2010] modeled current sheets from the THEMIS observations, creating background sheets with much colder plasma.…”
Section: Discussionmentioning
confidence: 99%